Strategi Manajemen Konflik TKW Pasca Perceraian (Studi Kasus di Desa Temurejo, Kecamatan Bangorejo, Kabupaten Banyuwangi) - Sayida, Belia Putri Hawa; Ningsih, Novia Rahayu; Shoumi, Zayyana Fajriati; Fitriana, Ani Qotus Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This journal discusses the problems related to divorce experienced by TKW in Tempurejo Bangorejo Village, Banyuwangi. The poverty rate is a trigger factor for the response that becoming a migrant worker is the only way that has a positive impact on family finances. but it turns out to provide a negative side also to result in divorce. This research uses a qualitative approach, so the research tends to be natural setting, with an emphasis on descriptive. Using an empirical approach and research directly related to reality. The method used is the observation method. Referring to this, the poverty rate in Banyuwangi is decreasing, but the economic conditions that remain unchanged make a wife's determination to become a TKW have positive hopes for the family's economy.